Do Manufacturing Performance leads to Green Supply Chain Practices? - Wan Mahmood, Wan Hasrulnizzam; Ab Rahman, Mohd Nizam; Md Deros, Baba (2011)
The concepts pertaining to greening the operation or supply chain are usually understood by industry as screening suppliers for their environmental performance and then doing business with only those that meet the regulatory standards. The driving forces for implementing the green concept into the company operations are many and comprise a range of reactive regulatory reasons to proactive strategic and competitive advantages reasons. However, if green practices are to be adopted by organizations in Malaysia, a demonstrate link between such measures and improving manufacturing performance is necessary. This paper identifies potential linkages between manufacturing performances that lead to green practices amongst a sample of companies in Malaysia. For this purpose a conceptual model was developed from literature sources and data collected using a structured questionnaire mailed to a sample of MS ISO 14001 certified manufacturing companies in Malaysia followed by structural equation modeling. The analysis identified that manufacturing performance leads to green supply chain practices.